Applications of 3D Bioprinting in Tissue Engineering and Regenerative Medicine - Gia Saini (MDPI AG, 2021)
Regenerative medicine is an emerging field that centers on the restoration and regeneration of functional components of damaged tissue. Tissue engineering is an application of regenerative medicine and seeks to create functional tissue components and whole organs. Using 3D printing technologies, native tissue mimics can be created utilizing biomaterials and living cells. Recently, regenerative medicine has begun to employ 3D bioprinting methods to create highly specialized tissue models to improve upon conventional tissue engineering methods. Here, we review the use of 3D bioprinting in the advancement of tissue engineering by describing the process of 3D bioprinting and its advantages over other tissue engineering methods. Materials and techniques in bioprinting are also reviewed, in addition to future clinical applications, challenges, and future directions of the field.